Death of a bachelorette [compact disc, unabridged] - Levine, Laura, 1943- (Levine, Laura, 1943- Jaine Austen mystery., 2017)
Jaine assumes working for a reality show in the tropics will be paradise, but instead it's frustrating, irritating, and deadly.